The Relevance of Patients' Spiritual Care in the Nigerian Cultural Context: A Health Care Chaplain's Perspective. (June 2019) - Aja, Victoria T.
In most Nigerian hospitals, there is no evidence of formally employed health care chaplains. Personal experiences of a health care chaplain serving at a faith-based hospital in Nigeria show that the Nigerian cultural context, as it relates to individuals' personal spirituality, as well as the abundant research on the associations between spirituality/religiosity and health, precipitate the need for services of health care chaplains in Nigerian hospitals, whether faith-based, non-faith-based, or government hospitals.